2021
DOI: 10.1007/s00268-021-06213-1
|View full text |Cite
|
Sign up to set email alerts
|

Prediction Model for Failure of Nonoperative Management of Uncomplicated Appendicitis in Adults

Abstract: Background Prediction of failure of nonoperative management (NOM) in uncomplicated appendicitis (UA) is difficult. This study aimed to establish a new prediction model for NOM failure in UA. Methods We included 141 adults with UA who received NOM as initial treatment. NOM failure was defined as conversion to operation during hospitalization. Independent predictors of NOM failure were identified using logistic regression analysis. A prediction model was established based on these independent predictors. Receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Previously, we reported that the maximal outer diameter of the appendix and presence of appendiceal fecalith were associated with failure of non-operative management in UA [22]. We considered that the presence of fecalith leads to an ongoing obstruction with subsequent out ow obstruction of the lumen of the appendix.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we reported that the maximal outer diameter of the appendix and presence of appendiceal fecalith were associated with failure of non-operative management in UA [22]. We considered that the presence of fecalith leads to an ongoing obstruction with subsequent out ow obstruction of the lumen of the appendix.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported various indicators associated with GPA [20][21][22][23][24][25][26][27][28][29][30][31][32]. WBC is commonly used as a blood marker for diagnosing appendicitis [21,22], while lymphocyte levels are inversely correlated with the severity of appendicitis in ammation, typically reduced in cases of gangrenous appendicitis [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we reported that the maximal outer diameter of the appendix and presence of appendiceal fecalith were associated with failure of non-operative management in UA [ 22 ]. We considered that the presence of fecalith leads to an ongoing obstruction with subsequent outflow obstruction of the lumen of the appendix.…”
Section: Discussionmentioning
confidence: 99%